Luteolin for the Treatment of Organ Fibrosis: A Mini Review - Wang, Nailong; Lan, Wei (Mini Reviews in Medicinal Chemistry, 2025)
Luteolin is a naturally occurring flavonoid that exhibits significant potential in mitigating organ fibrosis. This review consolidates evidence from studies demonstrating the antifibrotic effects of luteolin in hepatic, renal, cardiac, pulmonary, dermal, subretinal, and pancreatic fibrosis. Mechanistically, luteolin targets key pathways that drive fibrosis, including the TGF-β/Smad, STAT3, NF-κB, and AMPK signaling pathways, while suppressing oxidative stress, inflammation, and fibroblast activation. In hepatic fibrosis, luteolin inhibits hepatic stellate cell activation, reduces collagen synthesis, and counteracts ferroptosis by modulating the SLC7A11 and GPX4 pathways. Renal fibrosis is alleviated through the regulation of the SIRT1/FOXO3 and AMPK/NLRP3/TGF-β pathways, thereby attenuating ECM accumulation and inflammation. Cardiac benefits arise from luteolin’s modulation of NO-cGMP, AKT/GSK-3, and Nrf2/NF-κB axes, improving myocardial function. Pulmonary fibrosis models highlight the ability of luteolin to inhibit TGF-β1-induced Smad3 phosphorylation and inflammatory cytokine release. Additionally, luteolin demonstrates efficacy in skin and subretinal fibrosis by targeting TGF-β/Smad and YAP/TAZ pathways. Toxicology and pharmacokinetic studies indicate favorable safety profiles. Despite promising preclinical outcomes, clinical data remain scarce. The multi-target engagement, low toxicity, and broad bioactivity of luteolin position it as a compelling candidate for antifibrotic therapy. Further clinical research is warranted to translate these findings into therapeutic applications for fibrotic disorders.
Keywords: hepatic fibrosis